Heterotic GUT and standard model vacua from simply connected Calabi-Yau manifolds - Blumenhagen, Ralph; Moster, Sebastian; Weigand, Timo (Arxiv, 2006)
We consider four-dimensional supersymmetric compactifications of the E8 x E8 heterotic string on Calabi-Yau manifolds endowed with vector bundles with structure group SU(N) x U(1) and five-branes. After evaluating the Green-Schwarz mechanism and deriving the generalized Donaldson-Uhlenbeck-Yau condition including the five-brane moduli, we show that this construction can give rise to GUT models containing U(1) factors like flipped SU(5) or directly the Standard Model even on simply connected Calabi-Yau manifolds. Concrete realizations of three-generation models on elliptically fibered Calabi-Yau manifolds are presented. They exhibit the most attractive features of flipped SU(5) models such as doublet-triplet splitting and proton stability. In contrast to conventional GUT string models, the tree level relations among the Standard Model gauge couplings at the GUT scale are changed.
Gesehen am 09.01.2018